Induction of phagocytic activity and nitric-oxide production in natural populations of Trypanosoma Cruzi I and II from the state of Paraná, Brazil - Zalloum, Leila; Lala, Eliane Raquel Peres; Moreira, Neide Martins; Silveira, Thaís Gomes Verzignassi; Dalálio, Márcia Machado de Oliveira; Toledo, Max Jean de Ornelas; Gomes, Mônica Lúcia; Araújo, Silvana Marques de (Revista do Instituto de Medicina Tropical de São Paulo, 2011)
Twelve strains of Trypanosoma cruzi isolated from wild reservoirs, triatomines, and chronic chagasic patients in the state of Paraná, southern Brazil, and classified as T. cruzi I and II, were used to test the correlation between genetic and biological diversity. The Phagocytic Index (PI) and nitric-oxide (NO) production in vitro were used as biological parameters. The PI of the T. cruzi I and II strains did not differ significantly, nor did the PI of the T. cruzi strains isolated from humans, triatomines, or wild reservoirs. There was a statistical difference in the inhibition of NO production between T. cruzi I and II and between parasites isolated from humans and the strains isolated from triatomines and wild reservoirs, but there was no correlation between genetics and biology when the strains were analyzed independently of the lineages or hosts from which the strains were isolated. There were significant correlations for Randomly Amplified Polymorphic Deoxyribonucleic acid (RAPD) and biological parameters for T. cruzi I and II, and for humans or wild reservoirs when the lineages or hosts were considered individually.